2013
DOI: 10.3109/00207454.2012.755969
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exercise during pregnancy affects mitochondrial enzymatic activity and biogenesis in offspring brain

Abstract: The present study addresses whether exercise during pregnancy in mouse alters mitochondrial function in the brains of the resultant offspring. We divided pregnant mice into four groups: a control group and groups of mice that exercised for 20 (E20m), 30 (E30m) and 40 min/d (E40m). The pregnant mice ran on a treadmill at 12 m/min, 5 d/week for a duration of 3 weeks. The protein expression of cytochrome c oxidase subunit Va (CVa) was downregulated in the offspring of the E20m group, unlike that in the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Recently, it has been reported that maternal treadmill exercise (40 min daily/3 weeks) during pregnancy improved mitochondrial function in the brains of pups through a mechanism related to adaptive counterresponse to eliminate reactive species [38]. In the same way, maternal swimming exercise (30 min daily/4 weeks) improved antioxidant defenses and induced mitochondrial biogenesis in the brains of offspring [39].…”
Section: Neurobiological Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, it has been reported that maternal treadmill exercise (40 min daily/3 weeks) during pregnancy improved mitochondrial function in the brains of pups through a mechanism related to adaptive counterresponse to eliminate reactive species [38]. In the same way, maternal swimming exercise (30 min daily/4 weeks) improved antioxidant defenses and induced mitochondrial biogenesis in the brains of offspring [39].…”
Section: Neurobiological Mechanismsmentioning
confidence: 98%
“…Given the intrinsic relationship between energy production and mitochondria, it is not surprising that mitochondrial energy metabolism plays a pivotal role in how maternal exercise affects the synaptic plasticity and cognition of offspring [38,39].…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…In several rodent studies, maternal exercise is associated with increased offspring learning and memory ability [49][50][51][52] and reduced anxiety. 53 The cognitive and emotional improvements may be due to maternal exercise-induced increase in neural Bdnf (a neurotrophic factor associated with enhanced learning and memory abilities), especially in the hippocampus and prefrontal cortex, [51][52][53] , leptin (Lep, a satiety hormone), 49 Vegf (an angiogenic protein) in the prefrontal cortex, 53 and c-Fos (a proto-oncogene) expression in the perirhinal cortex.…”
Section: Maternal Exercise and Offspring Behavioral And Reproductive mentioning
confidence: 99%
“…53 The cognitive and emotional improvements may be due to maternal exercise-induced increase in neural Bdnf (a neurotrophic factor associated with enhanced learning and memory abilities), especially in the hippocampus and prefrontal cortex, [51][52][53] , leptin (Lep, a satiety hormone), 49 Vegf (an angiogenic protein) in the prefrontal cortex, 53 and c-Fos (a proto-oncogene) expression in the perirhinal cortex. 50 Further, maternal exercise may exert positive effects on brain mitochondrial function 51,54 and neuron cell numbers and viability. 49,52,55 Dendritic growth of parietal neurons is blunted in offspring of dams subjected to prenatal restraint stress.…”
Section: Maternal Exercise and Offspring Behavioral And Reproductive mentioning
confidence: 99%
“…In humans, in utero exercise exposure is associated with greater cognitive performance in early postnatal development [10] and higher intelligence scores at 5 years of age [9] relative to children of mothers that did not exercise during pregnancy. Numerous studies in rodents show that in utero exercise exposure increases hippocampal expression of brain derived neurotrophic factor (Bdnf) [4; 5; 7; 12]; cell proliferation and neuron differentiation [5; 6]; increased mitochondrial content and expression of genes associated with mitochondrial biogenesis [13]; and improved performance on spatial [4; 8] and non-spatial memory tasks [5; 7; 14]. In addition to the influence of maternal exercise, long-term paternal forced exercise enhances male offspring neurotrophin expression and spatial learning and memory performance [15], suggesting transgenerational inheritance of exercise effects beyond direct in utero exposure.…”
Section: Introductionmentioning
confidence: 99%